Impacts of the Rise of China on Developing Country Trade : Evidence from North Africa - Brenton, Paul (2012)
Despite the global financial and economic crisis, China has continued to experience strong export-driven growth and, indeed, became the world's largest exporting country in 2009. This rise of China in international markets presents African countries with growing competition in their home and export markets, but also with new opportunities. This paper focuses on the impacts of these developments on countries in North Africa, which are directly affected by the prominence of Chinese manufacturing. In particular, the analysis addresses two policy questions: first, is competition from China leading to substantial displacement of resources that incur significant adjustment costs while moving to new activities, or are there opportunities to exploit finer patterns of specialization that entail less disruption; and second, will policies that mitigate the impact of competition from China limit the longer-term capacity to exploit new opportunities in the global market? The findings from the empirical analysis suggest that policy makers can support North African producers in the increasingly fierce competition with China by reviewing the regulatory and incentives environment, reducing trade logistics costs, and broadening trade promotion efforts to non-traditional markets.